Dziecko w przedszkolu wobec dyrektywności i bezrefleksyjności nauczyciela – oblicza sytuacji trudnych w edukacji przedszkolnej - Sadowska, Katarzyna (Kultura-Społeczeństwo-Edukacja, 2025)
The research aims to show difficult situations in kindergarten that children encounter that result from teachers’ directiveness and thoughtlessness. In the difficult situations described in the study, the child is treated as an object and not only has to meet the requirements set by teachers but also faces misunderstanding of emotions, lack of respect, misunderstanding of needs resulting from the developmental period and – in some cases – violence and aggression if they cannot adapt to the applicable standards and submit to the “will” of the teacher. The author conducted participant observation, which she carried out from September to March of the 2024/2025 school year in two public kindergartens in Poznań. Participant observation in each facility was conducted twice a week during classes that the author of the study carried out with the children (each time the classes were held for half an hour for each group on one day, the classes were in the form of artistic workshops) and by participating in special events and rehearsals for these events. The researcher also stayed with the children during their activities in the kindergarten on the days when classes were conducted and accompanied the teachers. The observation was conducted based on the following criteria: − the teacher’s way of communicating with children; − the teacher’s reactivity to the children’s current needs; − the teacher’s reactions in difficult situations in contact with the child. The research results indicate that “little ones” in difficult situations often could not rely on their teacher, it was even observed that difficult situations were caused by this teacher. When the child could not adapt to the requirements placed on it, it was “disciplined”, and blackmailed, and attempts were made to underestimate its value, so it was harmed and intimidated.